The Role of MR Enterography in Assessing Crohn’s Disease Activity and Treatment Response - Matthew P. Moy; Jenny Sauk; Michael S. Gee (Gastroenterology Research and Practice)
MR enterography (MRE) has become the primary imaging modality in the assessment of Crohn’s disease (CD) in both children and adults at many institutions in the United States and worldwide, primarily due to its noninvasiveness, superior soft tissue contrast, and lack of ionizing radiation. MRE technique includes distention of the small bowel with oral contrast media with the acquisition of T2-weighted, balanced steady-state free precession, and multiphase T1-weighted fat suppressed gadolinium contrast-enhanced sequences. With the introduction of molecule-targeted biologic agents into the clinical setting for CD and their potential to reverse the inflammatory process, MRE is increasingly utilized to evaluate disease activity and response to therapy as an imaging complement to clinical indices or optical endoscopy. New and emerging MRE techniques, such as diffusion-weighted imaging (DWI), magnetization transfer, ultrasmall superparamagnetic iron oxide- (USPIO-) enhanced MRI, and PET-MR, offer the potential for an expanded role of MRI in detecting occult disease activity, evaluating early treatment response/resistance, and differentiating inflammatory from fibrotic strictures. Familiarity with MR enterography is essential for radiologists and gastroenterologists as the technique evolves and is further incorporated into the clinical management of CD.